2023
DOI: 10.1128/iai.00375-22
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component System YesMN Promotes Pneumococcal Host-to-Host Transmission and Regulates Genes Involved in Zinc Homeostasis

Abstract: The ability to sense and respond rapidly to the dynamic environment of the upper respiratory tract (URT) makes Streptococcus pneumoniae ( Spn ) a highly successful human pathogen. Two-component systems (TCSs) of Spn sense and respond to multiple signals it encounters allowing Spn to adapt and thrive in various host sites. Spn TCS have been implicated in their ability to promote pneumococcal c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
1
0
0
Order By: Relevance
“…While some studies have effectively used phosphomimetics ( 63 ), it is noteworthy that that while phosphorylation typically promotes subunit oligomerization and DNA binding, exceptions do exist ( 64 ). Our experience has shown that overexpressing native RRs in conjunction with RNA-sequencing reliably identifies RR targets; findings later confirmed by other studies ( 47 , 65 ). Consequently, the same methodology was adopted for this study.…”
Section: Discussionsupporting
confidence: 84%
“…While some studies have effectively used phosphomimetics ( 63 ), it is noteworthy that that while phosphorylation typically promotes subunit oligomerization and DNA binding, exceptions do exist ( 64 ). Our experience has shown that overexpressing native RRs in conjunction with RNA-sequencing reliably identifies RR targets; findings later confirmed by other studies ( 47 , 65 ). Consequently, the same methodology was adopted for this study.…”
Section: Discussionsupporting
confidence: 84%